Propuesta de una preformulación para el enmascaramiento del sabor amargo del activo en una tableta masticable de acetaminofén de 120 mg (2024)
This research work is based on a preformulation proposal for masking the bitter taste of the active ingredient in a 120 mg acetaminophen chewable tablet, seeking to obtain a more accessible pharmaceutical form for mainly geriatric, pediatric patients and those with difficulty swallowing conventional oral tablets. This proposal is based on the degree work entitled "Proposal for a preformulation for masking the bitter taste of the active ingredient in a 500 mg acetaminophen chewable tablet". Principally, the selection of the excipients that were part of the tentative formulation of the orodispersible tablet was made, then the possible taste masking agents of the active ingredient were identified and the mechanism by which the neutralization of the bitter taste was exerted was established, finally the pharmacotechnical characterization of the ingredients selected for the tentative formulation was performed. In conclusion, a preformulation with acceptable pharmacotechnical characteristics was obtained, through an experimental design allowed to demonstrate the masking of the bitter taste of the active ingredient.